Teachers' Strategies in Improving Students' Nationalism and Love for the Country in the Era of Globalization - Adrianus Bawamenewi; Anugerah Tatema Harefa; Berkat Persada Lase (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the teacher's strategy and challenges or obstacles in improving students' national insight and love for the country in the era of globalization. This research uses a qualitative method with a descriptive approach. The locations in this study were at Bunga Mawar Private Junior High School, BNKP Private Junior High School, Gunungsitoli Alo'oa State Junior High School 2 and BNKP AGIOS Nikolaus Private Junior High School, the four research locations chosen were in Gunungsitoli City, with Civics Teacher and student informants. The data collection techniques used are observation, interview and documentation techniques. Data analysis techniques in this study are data collection, data reduction, data presentation and data verification. From the results of the study, it was found that the Teacher's Strategy in Improving Students' Nationalism and Love for the Country in the Era of Globalization is to foster the value of nationalism in students through lessons, integrating nationalism and love for the country values to students in technology-based activities such as social media and the internet, implementing the values of Pancasila in the life of the school environment, inviting students to filter incoming information and culture in order to preserve traditional culture. Challenges in Improving Students' Nationalistic Insight and Love for the Country in the Era of Globalization, namely the development of technology can affect the mindset, attitude and action patterns of students in the nation and state, thus forgetting nationalistic insight. resulting in a conflict of values in students. Decreasing the moral quality of students, increasing social inequality, the emergence of fast-paced and instant traditions, difficult to organize and even against teachers. Schools have difficulty in restricting students from accessing social media and limited infrastructure to support students in participating in learning activities. Constraints in Improving Students' Nationalistic Insight and Love for the Country in the Era of Globalization lack of student awareness in applying the values or characters that have been taught, low parental concern for their children's education, changes in lifestyle that lead to unhealthy behavior, limited time owned by teachers to educate students in instilling moral values and love for the country.